The Role of Social Interest and Empathy on Helping Behaviors during Floods - Mazraeh , Nasrollah; Khodarahimi, Siamak; Hesam, Maeda; Rasti, Ali; Mirghobad Khodarahmi, Sahar; Aganj, Najme; Sheikhi, Sonay (Anales de Psicología / Annals of Psychology, 2023)
This study examined the role of social interest and empathy in helping and not helping adults during floods. Participants were split into two groups with helping behaviors (N = 90) and without helping behaviors (N = 90) during floods from six cities, Khuzestan province, Iran. A demographic questionnaire, the Social Interest Scale (SIS), and the Questionnaire Measure of Empathic Tendency (QMET)) were used in this study. Analysis showed that people in the helping group had higher social interest and empathy than those in the control group. This study can describe how, in the short, social interest and empathy would contribute to helping behaviors to flood-affected people for saving their life and properties. These findings can be combined with the emergency aid programs in natural disasters and will become public information.